Edukasi Perilaku Ibu Balita dengan Tindakan Pencegahan COVID-19 - Haryani, Sri; Misniarti, Misniarti; Astuti, Agnes Dewi (Journal of Telenursing (JOTING), 2023)
This research aims to find out how mothers with toddlers behave in procedures to prevent COVID-19 disease. The research method used is quantitative with a Quasi-Experimental design with pre-test and post-test. The results showed that more than half of the respondents had low education 16 (36.4%), and most worked 12 (27.3%). Mothers with toddlers have knowledge and attitudes with a p-value of 0.000 and actions with a p-value of 0.256. In conclusion, the mother's behavior in preventing COVID-19 disease is good. Keywords: Toddlers, COVID-19, Education, Prevention